THE EFFECT OF THE PROJECT-BASED LEARNING (PJBL) MODEL ON FISH-BASED FOOD PROCESSING ON THE COGNITIVE, PSYCHOMOTORIC, AND ENTREPRENEURIAL SPIRIT OF MTS STUDENTS - Mifrasah, Emy; Susmanti, Ika (Magister Program Studi Pendidikan Ekonomi, 2026)
This study aims to examine the effect of the Project-Based Learning (PjBL) model on cognitive learning outcomes, psychomotor skills, and entrepreneurial spirit of Madrasah Tsanawiyah (MTs) students on fish-based food processing material. Using a quantitative approach with a quasi-experimental design, this study compared the project-based experimental class (n=30) and the control class (n=28) who learned conventionally. Data analysis was conducted using the non-parametric Mann-Whitney U test. The results proved that PjBL had a highly significant positive effect (p < 0.05) overall; where the experimental class consistently outperformed the control class with a more even distribution of abilities. The novelty of this study lies in the successful integration of culinary vocational pedagogy with micro-scale edupreneurship incubation in early adolescence. Specifically, this study makes an important contribution to the literature on economic education by proving that entrepreneurial character, self-efficacy, and understanding of basic business calculations can be naturally cultivated through simulations of real-life project completion. The implications of these findings encourage educational institutions to transform rote curricula into product-based learning. This research recommends implementing mini-business ecosystems in schools, such as Market Day, to continuously bridge academic knowledge with real-world economic practices.